A suitable state-space model for renewable source-based microgrids with hydrogen as backup for the design of energy management systems. (1st September 2020) - Vivas, F.J.; Segura, F.; Andújar, J.M.; Caparrós, J.J.
Highlights: A methodological foundation to obtain a generalized model of a renewable source-based microgrid is proposed. A general state-space model that allows modelling the performance of a renewable source-based microgrid is developed. The developed general state-space model accurately reflects the behaviour of renewable source-based microgrids throughout its entire operating range. The developed general state-space model essentially accounts for relevant technical and economic parameters. The developed general state-space model allows to design control systems for renewable source-based microgrids. Abstract: This paper presents a methodological foundation to obtain a general state-space model for renewable source-based microgrids. The main novelty lies in developing a general control-oriented model that, taking into account all the parameters (technical and economic), enables the design of efficient energy management system (EMS) to make the best decisions both in the short-term (such as to adapt demand and production) and long-term (such as extending the lifespan of the most expensive and sensitive microgrid elements). The proposed approach guarantees a better approximation when compared to traditional models because most of them are linearized systems around a single operating point. The proposed model is more comprehensive since, apart from describing electrical performance for each device that makes up the microgrid, it also includes technical and economical parameters such as operating efficiency, degradation, losses and costs needed for microgrid optimization. The experimental results show the quality and excellent performance of the developed model. Additionally, a comparison between the reference models from the literature and the one proposed in this paper is undertaken. The results reflect a good performance in the evolution of the main parameters of the microgrid. Moreover, the use of the proposed methodology, based on the definition and calculation of the linear model parameters in each discretization period, guarantees a good fit of the model with respect to the non-linear behaviour of the microgrid.